Sniffles, sneezes, hiccups, and coughs - Durant, Penny Raife (London ; DK, 2005)
Presents a brief description of the causes and cures of respiratory problems such as sneezing and coughing.
Includes index.
3.7
K-3
Center for the Collaborative Classroom Curriculum
Keywords: Respiration -- Juvenile literature; Sneezing -- Juvenile literature; Cough -- Juvenile literature; Hiccups -- Juvenile literature; Respiration; Sneezing; Cough; Hiccups; Readers (Elementary)